Clinical Effects of Stereotactic Body Radiation Therapy Targeting the Primary Tumor of Liver-Only Oligometastatic Pancreatic Cancer - Ji, Xiaoqin; Zhao, Yulu; He, Chenglong; Han, Siqi; Zhu, Xixu; Shen, Zetian; Chen, Cheng; Chu, Xiaoyuan (Frontiers in Oncology, 2021)
Aim: To investigate the efficacy and safety of stereotactic body radiotherapy (SBRT) targeting the primary tumor for liver-only oligometastatic pancreatic cancer. Methods: We compared the efficacy and safety of SBRT plus chemotherapy with chemotherapy alone in patients with liver-only oligometastatic pancreatic cancer. The populations were balanced by propensity score-weighted and propensity score-matched analyses based on baseline variables. The primary outcome was overall survival (OS). The secondary outcomes included progression free survival (PFS), local progression, metastatic progression and symptomatic local control. Results: This is a retrospective study of 89 pancreatic cancer patients with liver-only oligometastasis. Overall, 34 (38.2%) and 55 (61.8%) patients received SBRT plus chemotherapy and chemotherapy alone, respectively. After propensity score matching, 1-year OS rate was 34.0% (95%CI, 17.8-65.1%) in the SBRT plus chemotherapy group and 16.5% (95%CI, 5.9-46.1%) in chemotherapy alone group (P=0.115). The 6-month PFS rate was 29.4% (95%CI, 15.4-56.1) in SBRT plus chemotherapy and 20.6% (95%CI, 8.8-48.6) in chemotherapy alone group (P=0.468), respectively. Further subgroup analysis indicated that the addition of SBRT improved OS in patients with primary tumor located in the head of pancreas (stratified HR, 0.28; 95% CI, 0.09 to 0.90) or good performance status (stratified HR, 0.24; 95% CI, 0.07 to 0.86). In terms of disease control, SBRT delayed local progression of pancreas (P=0.008), but not distant metastatic progression (P=0.56). Besides, SBRT offered significant abdominal/back pain relief (P=0.016) with acceptable toxicities. Conclusions: The addition of SBRT to chemotherapy in patients with liver-only oligometastatic pancreatic cancer improves the OS of those with primary tumor located in the head of pancreas or good performance status. In addition, it is a safe and effective method for local progression control and local symptomatic palliation in patients with metastatic pancreatic cancer.